An Android-based personalized public transportation advisor - Ferreira, J. C. (2018)
This work presents the development of a mobile application which allows the user to access real time data related with public transportation information. This application combines the geographic user context and preferences with the data provided by a public transportation information system, fulfilling the necessities of today’s passengers and providing an incentive for the population to use the public transportation infrastructure. The proposed application, still in prototype stage, allows the user to benefit from real time access to public transportation data in a simple and intuitive form. Results from use cases and real world tests using data from a Brazilian bus fleet operator were employed to validate the operability and features of the developed prototype.